The Old Testament Dietary Laws Was Abolished According To Mark 7:19b? - Harman Ziduhu Laia; Jimmy Sutrisno; Daniel Ari Wibowo (Theological Journal Kerugma, 2022)
Various essential discussions have been raised against Mark's parenthetical commentary in 7:19b, one of which is the discussion of eating from that statement. On the one hand, some take the text as a clear teaching of the Bible about the abolition of the food law in the Torah, as a result of which the law no longer binds both Jewish believers and Gentile believers. On the other hand, some consider it meaningless as the abolition of the food law in the Torah. Within this group, various meanings have been proposed. Historically, lexically, grammatically, and contextually it shows that Mark 7:19b is not a teaching of the abolition of the food law in the Torah, but a "guarantee" for the Gentile believers in Rome as Mark's gospel audience that there will be no unclean food for them because of contamination. or consumed with dirty hands (not washed), but the food is kept clean, so it cannot defile those who eat it. Therefore, Mark 7:19b will be of no significance to the reader if it is understood as teaching the abolition of the food law because they do not have binding laws on unclean and kosher food and need to be abolished, it is only given to the Jews. Therefore, for them, the food is kept clean. Even if the abolition of the food law in the Torah is done, it has nothing to do with Gentile believers.